Production of weak forms of prepositions by non-native speakers of English - Kozáková, Tereza (Univerzita Karlova, Pedagogická fakulta, 2021)
Cílem této bakalářské práce je odhalit a popsat, do jaké míry nerodilí mluvčí angličtiny s různými mateřskými jazyky používají slabé formy gramatických slov, konkrétně předložek. Teoretická část popisuje samohláskovou redukci a její význam pro rytmus v anglické větě. Následně je na tento koncept nahlíženo perspektivou Lingua Franca Core a jejím přístupem k výuce samohláskové redukce. Praktická část obsahuje analýzu nahrávek z korpusu nerodilých mluvčích angličtiny L2-ARCTIC, která popisuje, jestli a do jaké míry vybraní mluvčí arabštiny, hindštiny, korejštiny, mandarínské čínštiny, španělštiny a vietnamštiny redukují předložky v kanonicky slabých pozicích. Pozornost je věnována kvalitě a kvantitě samohlásek v předložkách s ohledem na výskyt na začátku či uprostřed věty. Průměrné trvání samohlásek v daných předložkách jsou porovnány s poměrnou délkou travní u samohlásek pro standartní britskou angličtinu. KLÍČOVÁ SLOVA ELF, předložky, poměrná délka samohlásek, samohlásková redukce, schwa, slabé formy This bachelor thesis aims to reveal and describe to which extent non-native speakers of English from different L1 backgrounds employ weak forms when producing prepositions. The theoretical part focuses on vowel reduction and its importance for the natural rhythm of English. This concept is further explored from the Lingua Franca Core perspective and its approach to teaching vowel reduction. In the practical part, the analysis of a series of recordings is carried out. The recordings were taken from the L2-ARCTIC speech corpus of non-native English (Arabic, Hindi, Korean, Mandarin, Spanish, and Vietnamese). The purpose of the analysis is to explore whether and how speakers with different L1s reduce vowels in canonically weak forms of prepositions. The focus is placed on the quality and quantity of vowels in said prepositions and their duration with regard to their occurrence in either initial or medial positions. The average vowel duration is then compared to the referential vowel duration in General British. KEY ...